PENGEMBANGAN INSTRUMEN TES KEMAMPUAN BERPIKIR KRITIS MATEMATIS DENGAN MENGGUNAKAN ANALISIS MODEL RASCH PADA SISWA SMP - Rionald Febriano; Edy Tandililing; Eny Enawaty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe low mathematical critical thinking ability of students. An appropriate measuringtool is needed to measure critical thinking processes, namely the analysis of the Raschmodel. This study aims to produce and develop a mathematical critical thinking abilitytest instrument using the Rasch model analysis and analyze the mathematical criticalthinking skills of eighth grade students of SMP Negeri 16 Pontianak. The constructionof this research is research and development with the type of research instrumentdevelopment Tessmer (1998). The research respondents were class VIII F students ofSMP Negeri 16 Pontianak for the 2020/2021 academic year who had studied SPLDVmaterial. Mathematical critical thinking ability test instrument was developed with aformative research phase, namely the preliminary phase (preparation and design ofquestions); and the formative evaluation phase (expert review, one-on-one test, smallcluster scale with Rasch model analysis and large-scale test). Fulfillment of indicatorsof accuracy so that those developed can be used to measure critical thinking skillsmathematically. Mathematically critical thinking skills in class VIII SMP Negeri 16Pontianak are high; high for indicators of ability to interpret and analyze, and moderatefor indicators of ability to evaluate.Keywords: Instrument Development, Mathematical Critical Thinking Ability TestInstrument, Rasch Model Analysis